Ten trillion and counting [videorecording (DVD)] - Sawyer, Forrest (WGBH Educational Foundation ; Distributed by PBS Home Video, 2009)
"All of the federal government's efforts to stem the tide in the financial meltdown that began with the subprime mortgage crisis have added hundreds of billions of dollars to the national debt. FRONTLINE reports on how this debt will constrain and challenge the new Obama administration, and on the growing chorus on both sides of the aisle that without fiscal reform, the United States government may face a debt crisis of its own, which makes the current financial situation pale in comparison. Through interviews with leading experts and insiders in government finance, the film investigates the causes and potential outcomes of -- and possible solutions to -- America's $10 trillion debt." -- Container.